EFEKTIVITAS PEMBELAJARAN BERDIFERENSIASI MELALUI MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR IPAS KELAS 5 DI SDN KARANGTENGAH 01 BATANG - Rohmah, Lathifatul; fajriyah, Khusnul; Wijayanti, Arfilia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the lack of student participation in learning which resulted in low student learning outcomes. This is due to the use of inappropriate learning methods. The problem in this research is whether differentiated learning through the PBL model is effective on the science learning outcomes of grade 5 students at SDN Karangtengah 01 Batang? The aim that the researcher wants to achieve in this research is to determine the effectiveness of differentiated learning through the science and science learning outcomes of grade 5 students at SDN Karangtengah 01 Batang. This research is a quantitative research using a design Pre-Experimental Design in the form of One-Group Pretest-Posttest Design. The population in this study were all 5th grade students at SDN Karangtengah 01 Batang. The sample in this study used one class in grade 5 of SDN Karangtengah 01 Batang, namely 18 students. Sampling used a saturated sampling technique. This data was obtained through observation, interviews and tests. Based on calculations, the pretest results obtained were 22% of students who completed it with an average score of 69. Meanwhile, the posttest results were 88% of students who completed it with an average score of 86. The t test analysis states that the t count is 8.531. Because t count > t table, namely 8.531 > 1.740, H0 is rejected and Ha is accepted. It can be concluded that differentiated learning through the PBL model is effective on the learning outcomes of grade 5 students at SDN Karangtengah 01 Batang. Based on the results of this research, the suggestion that can be made is that the differentiated learning model through the PBL model can be used by teachers as an alternative method in teaching science subjects.